Analysis of HIV/AIDS Mitigation Strategies through the Penta Helix Model in Surabaya - Utomo, S. Andre Prasetyo; Kriswibowo, Arimurti (Journal La Sociale, 2024)
HIV/AIDS is a highly dangerous disease, thus posing a serious concern for the Surabaya city government, especially considering Surabaya has the highest cases in East Java. It is imperative for the Surabaya city government to address this health issue with special attention to prevent further spread. This research aims to analyze Prevention Transmission Strategies through the Penta Helix Model in Surabaya. The research methodology employed is qualitative descriptive. The study was conducted at the Surabaya City Health Office, Orbit Surabaya Foundation, Radio Republik Indonesia Surabaya, Academia, and Private sectors. The findings indicate that (1) Prevention strategies conducted by the Surabaya City Health Office in preventing the transmission of HIV/AIDS cases in Surabaya need improvement, particularly due to the increased number of HIV cases compared to the previous year. (2) Prevention of HIV/AIDS transmission in Surabaya through the Penta Helix Model concept has not been effectively implemented. (3) Prevention of HIV/AIDS transmission in Surabaya lacks collaboration with media, private sectors, and academia.